Measuring the no-load running torque of RV reducer based on the SVD and MCSA. (28th February 2022) - Yu, Zhen; Qiu, Zurong; Li, Hao; Xue, Jie; Zhao, Lianyu
Highlights: A new method of testing the RV reducer's no-load running torque is proposed. The characteristics of the additional torque are analyzed. The no-load running characteristics of the RV reducer are analyzed. The method provides a reference for the torque test of the RV reducer. Abstract: At present, torque sensors are commonly used in industry to measure the idle torque of the Rotary Vector (RV) reducer. Since the additional torque from the measuring instrument itself is included in the torque sensor's measurement results, the torque sensor's reading value cannot be used as the actual no-load operation torque of the RV reducer. In this paper, the characteristics of the additional torque produced by the instrument and the no-load running characteristics of the RV reducer are analyzed. A method of using singular value decomposition (SVD) filtering and motor current signature analysis (MCSA) to test the no-load running torque is proposed to eliminate the influence of additional torque caused by the inevitable structure problems of the instrument. The measurement steps of no-load running torque using the proposed method are introduced, and the measurement experiment from low speed to high speed is carried out under no-load conditions. The experiment results show that the measurement error of the proposed method is less than 0.01Nm. It provides a reference for the measurement and evaluation of RV reducer torque performance in no-load operation.